Kepuasan Kerja Karyawan Dalam Industri Perhotelan: Tinjauan Work Life Balance, Lingkungan Kerja, Dan Beban Kerja - Kadek Ira Puspita Dewi; Ni Putu Ayu Sintya Saraswati; Sapta Rini Widyawati (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The abuse of human beings into humane workers to achieve goals is known as human resource management. Since employee satisfaction is a major component in utilizing existing human resources, companies must pay special attention when utilizing available human resources. This study aims to determine how work-life balance, work environment, and workload affect employee job satisfaction at The Kirana Bali Hotel & Spa. The population of this study consisted of 143 employees involved in this study, and the sample in this study consisted of 59 respondents, selected using proportionate stratified random sampling technique and calculated with the Slovin formula (e = 10%). The Coefficient of Determination, Validity Test, Reliability Test, Classic Assumption Test, Multiple Linear Regression Analysis, Multiple Correlation Test, and T-Test are included to analyze the data. This study found that work-life balance had a positive and significant impact on employee job satisfaction at The Kirana Bali Hotel & Spa, the work environment had a positive and significant impact on employee job satisfaction at The Kirana Bali Hotel & Spa, and workload had a negative and significant impact on employee job satisfaction at The Kirana Bali Hotel & Spa. The Kirana Bali Hotel & Spa. The results of this study indicate that a better life balance is a positive outcome. To further deepen and generalize the findings, it is recommended that researchers expand the study by including additional variables and expanding the research subjects.